Chronic small vessel disease affects clinical outcome in patients with acute striatocapsular stroke - Held, Valentin; Szabo, Kristina; Bäzner, Hansjörg; Hennerici, Michael G. (Cerebrovascular diseases, 2012)
Background: Recovery from stroke is presumed to be a function of a cerebral network. Chronic small vessel disease (SVD) has been shown to disrupt this network’s integrity and has been proposed as a predictor of poor outcome after stroke. We studied this hypothesis in patients with acute ischemic stroke of the striatocapsular region, an area of pronounced cortical and subcortical connectivity. Methods: We identified 62 patients with isolated striatocapsular stroke from our stroke registry. The standardized workup included clinical rating according to the modified Rankin Scale (mRS) and MRI, rated according to the Fazekas scale for the extent of SVD, ranging from grade 0 to III. MRS at admission, at discharge, and a short-term recovery parameter (the difference between mRS at admission and discharge) were correlated with the extent of SVD. Comorbidity was assessed with the Charlson comorbidity index (CCI). Results: SVD was graded 0 in 7%, I in 60%, II in 18%, and III in 16% of patients. The median mRS at discharge for the groups was 2, 1, 2 and 4, and the median recovery parameter was 2, 1, 1 and 0.5, respectively. The extent of SVD significantly correlated with both the mRS at discharge and the recovery parameter. While age was also a significant predictor of these outcome parameters, SVD severity was a significant predictor even after correction for age or CCI. Conclusions: SVD is a predictor of poor outcome and recovery in striatocapsular stroke, independent of age or comorbidity. Severe SVD disturbs the integrity of the cerebral network leading to aggravation of and poor recovery from neurological deficits.
Published online: December 13, 2011
Gesehen am 25.04.2018